Japanization at Work - Spencer, Bruce (Relations industrielles / Industrial Relations, 1994)
The article reviews the book, "Japanization at Work," by John Bratton.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z